Internet surveillance after Snowden: A critical empirical study of computer experts' attitudes on commercial and state surveillance of the Internet and social media post-Edward Snowden. Issue 4 (23rd November 2017) - Fuchs, Christian; Trottier, Daniel
Abstract : Purpose: This paper aims to present results of a study that focused on the question of how computer and data experts think about Internet and social media surveillance after Edward Snowden's revelations about the existence of mass-surveillance systems of the Internet such as Prism, XKeyscore and Tempora. Computer and data experts' views are of particular relevance because they are confronted day by day with questions about the processing of personal data, privacy and data protection. Design/methodology/approach: The authors conducted two focus groups with a total of ten experts based in London. As London is considered by some as the surveillance capital of the world, and has a thriving Internet industry, it provided a well-suited context. Findings: The focus group discussions featured three topics that are of crucial importance for understanding Internet and social media surveillance: the political economy surveillance in general; surveillance in the context of the Snowden revelations; and the question what the best political reactions are to the existence of a surveillance-industrial complex that results in political and economic control of the Internet and social media. The focus groups provided indications that computer and data experts are pre-eminently informed on how Internet surveillance works, are capable of critically assessing its implications for society and have ideas about on what should be done politically. Originality/value: Studies of privacy and surveillance after Edward Snowden's revelations have taken on a new dimension: Large-scale covert surveillance is conducted in a collaborative endeavour of secret services, private communications corporations and security companies. It has become evident that a surveillance-industrial Internet surveillance complex exists, in which capitalist communications and security corporations and state institutions collaborate.